Competition or Cooperation? A New Era for Agricultural Water Management - Ward, Christopher; Darghouth, Salah; Minasyan, Gayane; Gambarelli, Gretel (World Bank, Washington, DC, 2012)
Reliable supplies of water for agriculture have helped meet rapidly rising demand for food in developing countries, making farms more profitable, reducing poverty, and helping vast regions of the world develop more dynamic and diversified economies. Can these successes be sustained with demand for food rising and water resources waning? That is the challenge now facing policy makers, planners, and practitioners in agricultural water management (AWM), as well as their allies in the World Bank and other development organizations.